The extrapolated reference values procedure: Theory, algorithm, and results in patients and control subjects - Nandedkar, Sanjeev D.; Sanders, Donald B.; Hobson‐Webb, Lisa D.; Billakota, Santoshi; Barkhaus, Paul E.; Stålberg, Erik V. (Muscle & nerve, 2018)
ABSTRACT Introduction: Reference values (RVs) are required to separate normal from abnormal values obtained in electrodiagnostic (EDx) testing. However, it is frequently impractical to perform studies on control subjects to obtain RVs. The Extrapolated Reference Values (E‐Ref) procedure extracts RVs from data obtained during clinically indicated EDx testing. We compared the E‐Ref results with established RVs in several sets of EDx data. Methods: The mathematical basis for E‐Ref was explored to develop an algorithm for the E‐Ref procedure. To test the validity of this algorithm, it was applied to simulated and real jitter measurements from control subjects and patients with myasthenia gravis, and to nerve conduction studies from patients with various conditions referred for EDx studies. Results: There was good concordance between E‐Ref and RVs for all evaluated data sets. Discussion: E‐Ref is a promising method to develop RVs. Muscle Nerve 57: 90–95, 2018